2007
DOI: 10.1158/1535-7163.mct-07-0009
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiles for the NCI-60 cancer cell panel

Abstract: Advances in the understanding of cancer cell biology and response to drug treatment have benefited from new molecular technologies and methods for integrating information from multiple sources. The NCI-60, a panel of 60 diverse human cancer cell lines, has been used by the National Cancer Institute to screen >100,000 chemical compounds and natural product extracts for anticancer activity. The NCI-60 has also been profiled for mRNA and protein expression, mutational status, chromosomal aberrations, and DNA copy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
176
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(190 citation statements)
references
References 45 publications
(43 reference statements)
13
176
0
1
Order By: Relevance
“…As such, they have been used extensively as experimental models of cancer. In general, the expression patterns of the different cell-lines seen in the National Cancer Institute's NCI60 microarray are relatively consistent with the primary tissue type when the clustering is based on mRNA expression patterns 437,438 .…”
Section: The Expression Profile Of Bfl-1 In the Nci60 Microarraymentioning
confidence: 88%
See 2 more Smart Citations
“…As such, they have been used extensively as experimental models of cancer. In general, the expression patterns of the different cell-lines seen in the National Cancer Institute's NCI60 microarray are relatively consistent with the primary tissue type when the clustering is based on mRNA expression patterns 437,438 .…”
Section: The Expression Profile Of Bfl-1 In the Nci60 Microarraymentioning
confidence: 88%
“…These celllines have been examined by microarray analysis for gene expression patterns to give an NCI60 array 437 , which has been used to examine mRNA and protein expression, chromosomal aberrations, DNA copy number and mutational status, with all this data made available as a public resource (http://biogps.gnf.org/). In fact a selection of ninety three cell-lines derived from twenty two different cancer types are now present in the array 438 .…”
Section: The Expression Profile Of Bfl-1 In the Nci60 Microarraymentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the anticancer mechanisms of oridonin, we generated oligonucleotide DNA arrays for detection of miRNA expression because accumulating evidence suggested that miRNA expression profiling could be used as a tool to understand responses to therapy in human cancers (24,25). We found that 14 miRNAs were upregulated and 12 miRNAs were downregulated by more than 2-fold upon oridonin treatment, primarily representing the let-7 miRNA family and the miR-17-92 paralogous clusters (including the miR-17-92 cluster, miR-106a-363 cluster, and miR-106b-25 cluster), respectively ( Fig.…”
Section: Mirna Expression Profiling Reveals That C-myc Is a Target Ofmentioning
confidence: 99%
“…To assess the potential roles of microRNAs in cancer chemotherapy, we (31) have measured the expression levels of most known microRNAs in 60 human cancer cell lines (the NCI-60) used by the Developmental Therapeutics Program of the National Cancer Institute to screen >100,000 compounds as potential anticancer drug agents (1,32). Analogous molecular profiling of mRNA had previously enabled us to identify the genes involved in drug response by assessing the correlations between mRNA expression levels and the potencies of the tested compounds (for example, see refs.…”
Section: Introductionmentioning
confidence: 99%